PRAKTIK IMPUNITY DALAM KASUS PELANGGARAN HAM BERAT (TINJAUAN TERHADAP KASUS PEMBANTAIAN RAWAGEDE 1947) - Erika Erika; Abdul Rahman; Chairul Bariah (Journal of USU International Law, 2013)
ABSTRACT Impunity is one of the most often thing that ever happened in order to settle the gross human rights violations. Impunity means crime without punishment and an inevitable phenomenon in gross human rights violations’ cases. In the scope of international law, impunity refers to the failure to bring perpetrators of gross human rights violations to justice and denial of the right of victims to obtain justice and their right to redress. Impunity allows the cycle of human rights violations keeps going on, because the persons who committed the violations are not considered responsible. The 1947 Rawagede massacre case is an old case that began to become a hot topic which discussed by many recently ever since the case was taken to the Hague District Court in 2009. Therefore, the problems in this thesis are about the position of impunity in human rights violations’ cases, the international laws that related to the practice of impunity and how that happened in the case of the 1947 Rawagede massacre case. The research methodology used in this thesis is a normative legal research or library research, by collecting materials from books, journals, websites, legislations and other scientific papers which are closely related to the intentions and purposes of the preparation of this manuscript. Internationally, there are a few regulations which can be applied in this topic, because the scope is about human rights. First of all is the contents in the 1948 Universal Declaration of Human Rights. The second, for the assertion is the contents in the 1993 Vienna Declaration and Programme of Action. Last but not least, for the regulations on gross human rights violations are the contents in the 1998 Rome Statute. But because Indonesia has not ratified the 1998 Rome Statute and this events occurred long before the Rome Statute generated, then the case was submitted to the Hague District Court. As the result of this study, the conclusion is that the practice of impunity itself, even though not inevitable, still will not release the offenders from their responsibilities towards the victims of gross human rights violations because the victims have basic legal rights that must be fulfilled.